Woman in The Vulnerability and Disaster Risk of Merapi Eruption - Hastuti, Hastuti; Widodo, Edi; Giyarsih, Sri Rum (Universitas Lambung Mangkurat, 2024)
This study was aimed to depict the characteristics of women's vulnerability, as well as to study and analyze their efforts to reduce the disaster risk of Merapi eruption. This research is a survey research using descriptive quantitative method. The results showed that women were vulnerable in terms of their financial security, particularly due to their lack of bank saving, protection in the place of business, land, and residence. Their social vulnerability was shown by how most of the women and elderly people in the households of the area under study required protection when disaster occurred. The vulnerability in organizations was due to the lack of organizations to care for the women.